Financial Literacy Can Overcome Barriers To MSME Financing: Evidence From Indonesia - Suidarma, I Made; Widiantari, Komang Sri; Masno, Masno; Sukarnasih, Desak Made; Armanid, Aura; Marsudiana, I Dewa Nyoman (LPPM ISNJ Bengkalis, 2024)
This study aims to analyze the influence of financial literacy, debt management literacy, budgeting literacy, banking service literacy, and bookkeeping literacy on financing constraints for Micro, Small, and Medium Enterprises (MSMEs). The research population comprises 16,574 MSMEs in Badung Regency, Bali, Indonesia. This study uses primary data from questionnaires distributed via social media using Google Forms to respondents according to the criteria. The data collection technique used a questionnaire consisting of respondents' identities and six points related to financial literacy, measured by a 5-point Likert scale. Sampling used random sampling; the number of samples was measured using the Yamane formula approach to obtain a sample of 391 MSMEs. The data analysis method uses SEM-PLS, with the help of the SmartPLS tool, to test external models, internal models, and hypotheses. The study results revealed that financial literacy, debt management literacy, budgeting literacy, banking service literacy, and bookkeeping literacy positively influence financial constraints in MSMEs. A better understanding of debt management and bookkeeping also reduces financial constraints. This research expands the financial management theory by integrating five dimensions of financial literacy in one comprehensive model, which helps MSMEs improve financial literacy and reduce barriers to access to financing for sustainable business growth.